2021
DOI: 10.1038/s41467-021-24043-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics profiling of primary small cell carcinoma of the esophagus reveals RB1 disruption and additional molecular subtypes

Abstract: Primary small cell carcinoma of the esophagus (PSCCE) is a lethal neuroendocrine carcinoma. Previous studies proposed a genetic similarity between PSCCE and esophageal squamous cell carcinoma (ESCC) but provided little evidence for differences in clinical course and neuroendocrine differentiation. We perform whole-exome sequencing, RNA sequencing and immunohistochemistry profiling on 46 PSCCE cases. Integrated analyses enable the discovery of multiple mechanisms of RB1 disruption in 98% (45/46) of cases. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…It is known that SCNECs have similar histologic features and highly aggressive behavior across organ systems. In the lung, most harbor concurrent TP53 and RB1 mutations42 also frequent in gastrointestinal and pancreatic SCNECs 31,43,44. Several studies have analyzed the molecular features of cervical SCNECs22–25 reporting recurrent alterations in PI3K/AKT/mTOR (most frequently PIK3CA and PTEN ), RAS/MAPK pathways (most frequently KRAS ), as well as MYC and less frequently in TP53 and rarely in RB1 , a mutational profile closer to that reported in common cervical carcinomas8 and other HPV-associated malignancies including head and neck NECs 45–48.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It is known that SCNECs have similar histologic features and highly aggressive behavior across organ systems. In the lung, most harbor concurrent TP53 and RB1 mutations42 also frequent in gastrointestinal and pancreatic SCNECs 31,43,44. Several studies have analyzed the molecular features of cervical SCNECs22–25 reporting recurrent alterations in PI3K/AKT/mTOR (most frequently PIK3CA and PTEN ), RAS/MAPK pathways (most frequently KRAS ), as well as MYC and less frequently in TP53 and rarely in RB1 , a mutational profile closer to that reported in common cervical carcinomas8 and other HPV-associated malignancies including head and neck NECs 45–48.…”
Section: Discussionmentioning
confidence: 79%
“…In the lung, most harbor concurrent TP53 and RB1 mutations 42 also frequent in gastrointestinal and pancreatic SCNECs. 31,43,44 Several studies have analyzed the molecular features of cervical SCNECs [22][23][24][25] reporting recurrent alterations in PI3K/AKT/mTOR (most frequently PIK3CA and PTEN), RAS/MAPK pathways (most frequently KRAS), as well as MYC and less frequently in TP53 and rarely in RB1, a mutational profile closer to that reported in common cervical carcinomas 8 and other HPVassociated malignancies including head and neck NECs. [45][46][47][48] In addition, while mutations in pulmonary SCNECs have been shown to have a tobacco-related signature, 42,49,50 cervical SCNECs have aging-related and APOBEC signatures, 25,26 akin to the molecular signatures of HPV-associated tumors including cervical and head and neck carcinomas.…”
Section: Discussionmentioning
confidence: 97%
“…Li et al recently demonstrated that regional lymph node staging is an independent prognostic factor for patients with PSCCE. Their results showed that the MST at stage N0 was longer than that at stage N1, N2, and N3 (22.5 versus 22.2 versus 10.7 versus 9.7 months, respectively; P < 0.001), and patients with limited lymph node metastasis have a good prognosis [ 18 ]. Xu and his colleagues also showed that N0 patients had longer MST than N1, N2, or N3 patients (39.0 versus 28.0 versus 20.0 versus 14.0 months, respectively; P < 0.001) by univariate analysis and Cox regression analysis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is known heterogeneity across EP-NEC sites of origin with regard to survival outcomes, proportion of SC and non-SC subtypes [2] and genomic features [28]. In fact, EP-NECs at different sites of origin have a variable prevalence of "site-specific" molecular features, mainly shared with non-neuroendocrine cancers from the same organs, as well as of TP53 and RB1 mutations (virtually ubiquitous in SCLC) [8,[35][36][37]. It would be interesting to explore whether and how the morphological subtype plays a role in generating this inter-site biological diversity.…”
Section: Discussionmentioning
confidence: 99%